2016
DOI: 10.1111/ecin.12331
|View full text |Cite
|
Sign up to set email alerts
|

Fiscal Federalism, Decentralization, and Economic Growth: A Meta‐analysis

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(76 citation statements)
references
References 77 publications
2
65
0
9
Order By: Relevance
“…The results are manifold and point in all sorts of directions. Surprisingly, early papers from the 1990s yielded little in the way of consensus about the benefits of fiscal decentralization for economic activity, but the findings have been changing recently (Blöchliger, 2013;Kim, 2013;Asatryan, 2010;Baskaran, Feld and Schnellenbach, 2009). …”
Section: Fiscal Decentralization and Economic Growth In Colombia: Evimentioning
confidence: 99%
“…The results are manifold and point in all sorts of directions. Surprisingly, early papers from the 1990s yielded little in the way of consensus about the benefits of fiscal decentralization for economic activity, but the findings have been changing recently (Blöchliger, 2013;Kim, 2013;Asatryan, 2010;Baskaran, Feld and Schnellenbach, 2009). …”
Section: Fiscal Decentralization and Economic Growth In Colombia: Evimentioning
confidence: 99%
“…A recent metaanalysis, based on 31 empirical studies, found that the evidence on the effect of decentralisation on growth is inconclusive (Baskaran et al, 2014). The failure to find clear-cut results partly reflects problems of measuring the autonomy of sub-federal jurisdictions accurately.…”
mentioning
confidence: 99%
“…Estimated coefficients, by contrast, would not be comparable as the variables in our sample are not dimensionless, i.e. the studies employ different units and constructs (Baskaran et al (2014)). The dependent and independent variables used in primary studies are, for example, scaled differently (e.g.…”
Section: Methodsmentioning
confidence: 88%
“…46 For further meta-regression analysis relying on t-values, see Card et al (2010); Baskaran et al (2014); Klomp and de Haan (2010); Heinemann et al (2016). 47 In order to obtain this value, individual study results are combined to an overall or consensus estimate with respect to the size of effects by assuming between-study homogeneity (see Heinemann et al (2016), p. 9).…”
Section: Methodsmentioning
confidence: 99%